(untitled) (Journal of the Bangladesh Agricultural University, 2012)
A four week experiment was conducted to evaluate the effect of isoproteinous (35%) feed prepared named diet 1, 2, 3 and 4 respectively by substituting 0%, 50% , 75% and 100% fish meal with meat and bone meal in view of preparing a cost effective tilapia (Oreochromis niloticus) fry feed. The four experimental diets (diet 1 to 4) each were randomly assigned to twelve hapas with three replications. Tilapia fry (0.011g) were randomly stocked in 100 fry/9ft² hapa and fed five times a day up to their apparent satiation. The results of the study showed that the weight gain, specific growth rate (SGR), the apparent net protein utilization value and survival (%) of the fish were significantly (P<0.05) higher and better feed utilization with lower FCR value was observed in fish fed on the diet 4 where meat and bone meal was used as sole source of protein base. There was no significant difference between the carcass moisture and lipid of fish fed with different experimental diets. The results of the study indicated that diet 1 containing fish meal (45.15% Fish meal, 27.43% Rice bran and 27.43% Wheat flour) can be replaced by meat and bone meal containing diet 4 (54.06% Meat and bone meal, 22.97% Rice bran and 22.97% Wheat flour) with no adverse effects on growth and survival of O. niloticus. Before recommendation several trials will be necessary in different farms to be sure of the reproducibility of the result obtained in the present experiment. Cost- benefit analysis reveals that the meat and bone meal containing diet certainly provides cheaper feed. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12110 J. Bangladesh Agril. Univ. 10(1): 169174, 2012